POLA MAKAN DAN STATUS GIZI ANAK DI KOTA MEDAN: STUDI LONGITUDINAL TENTANG GAYA HIDUP DAN KESEHATAN - ALEX MARULI TUA LUMBANRAJA (JURNAL ILMIAH MAKSITEK, 2021)
The nutritional status of children in Medan City becomes unbalanced, where from the level of health many foods available to children are not suitable for nutrition, so that nutritional status is not suitable for consumption, where there are still some children in various areas in Medan City who experience malnutrition problems, thus affecting growth and also mindset when he grows up. This study used descriptive longitudinal analytical method. The population of this study amounted to 29,100 people who experienced reproductive health problems, where reproductive health problems would cause sexual diseases. The population of this study amounted to 650 children who experienced irregular eating patterns and poor nutritional status in Medan City, where the sample taken amounted to 70 children who experienced irregular eating patterns and malnutrition status in Medan City. The results stated that the number of children who experienced poor diet and nutritional status were children in the East Medan District area in the age range of 16-19 years, where children experienced poor diet and nutritional status, because the food nutrition provided did not contain good nutrients.